2003
DOI: 10.1080/02678290310001605910
|View full text |Cite
|
Sign up to set email alerts
|

Electro-optic properties of thiol-ene polymer stabilized ferroelectric liquid crystals

Abstract: Electro-optic properties of polymer stabilized ferroelectric liquid crystal (PSFLC) systems are examined as a function of varying concentrations of either a linear or crosslinked thiol-ene polymer. The thiol-ene method of polymer stabilization is a drastic change from previous studies designed to avert the problem of polymer phase separation. FLC rise time and tilt angle measurements were used to determine the effects of the polymer network on the optical properties of the system. The addition of monomer impur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Since the response time τ is directly proportional to the effective viscosity η via τ = η/P S E, the equivalent trend is also observed for the viscosity as a function of polymer network content ( Figure 9b ). Such behaviour has been reported by several authors [ 52 55 ], but it should be pointed out, that results of the opposite behaviour have also been published, i.e. , an increase in viscosity with increasing polymer concentration [ 56 ].…”
Section: Effects On Smc* Materials Parameterssupporting
confidence: 65%
“…Since the response time τ is directly proportional to the effective viscosity η via τ = η/P S E, the equivalent trend is also observed for the viscosity as a function of polymer network content ( Figure 9b ). Such behaviour has been reported by several authors [ 52 55 ], but it should be pointed out, that results of the opposite behaviour have also been published, i.e. , an increase in viscosity with increasing polymer concentration [ 56 ].…”
Section: Effects On Smc* Materials Parameterssupporting
confidence: 65%
“…9 Since then, thiol-ene reactions have undergone considerable investigation to determine monomer effects on polymerization rates, 1,[10][11][12][13][14][15][16] effects of oxygen, 7,8,17 effects of a thiol-olefin charge-transfer complex and the co-oxidation reaction, [18][19][20][21] thiol-(meth)acrylate copolymerizations, 6,22,23 initiatorless polymerizations, 8,22,24 and applications to polymer stabilized liquid crystals. [25][26][27][28] However, several aspects of thiol-ene polymerizations, including reaction order and kinetics, 2,3 initiation without photoinitiators, 8,22,24 and the dark reaction 19,20,29,30 are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 As a result, several novel applications of thiol-ene polymers have been investigated including dental composites, 46,47 holographic gratings, [48][49][50] biodegradable materials for tissue engineering, [51][52][53] formation of nanoimprinted polymers [54][55][56] and stabilizing and aligning liquid crystals in polymer matrices. 50,57,58 Recently, Lee and Bowman used thiol-ene photopolymerizations for modifying silica nanoparticles using a variety of thiol-ene monomers and reaction conditions. 59 Using real-time infrared spectroscopy, it was shown that, even in the presence of a significant amount of nanoparticles, near-complete conversion of the monomers was achieved in most cases including the cases where multifunctional monomers forming cross-linked polymer structures were used.…”
Section: Introductionmentioning
confidence: 99%